1984
DOI: 10.1007/bf01887807
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomographic distinction of submucosal lipoma and adenomatous polyp of the colon

Abstract: Described here is a patient with 2 large pedunculated colonic tumors detected by barium enema radiography. By computed tomography (CT) 1 was found to be a submucosal lipoma characterized by oval shape, smooth demarcation, and homogeneous density with a CT number of -68 HU, whereas the other was an adenomatous polyp with slightly fuzzy outline and a much higher CT number. This case indicates that CT can be a definitive diagnostic modality for distinguishing between a colonic lipoma and other solid or cystic tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
2

Year Published

1986
1986
1996
1996

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 18 publications
(25 reference statements)
0
5
2
Order By: Relevance
“…In a series of 14 adults with intussusception evaluated by CT, one case was secondary to lipoma and demonstrated diagnostic low attenuation [4], a finding supported by a small number of case reports [1][2][3][4][5][6][7][8]. In our series, however, we have shown that not all intussuscepted lipomas were characterized by homogeneous low attenuation on CT and may be mistaken for other neoplastic causes of intussusception, such as adenocarcinoma, lymphoma, and metastasis [3,4].…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…In a series of 14 adults with intussusception evaluated by CT, one case was secondary to lipoma and demonstrated diagnostic low attenuation [4], a finding supported by a small number of case reports [1][2][3][4][5][6][7][8]. In our series, however, we have shown that not all intussuscepted lipomas were characterized by homogeneous low attenuation on CT and may be mistaken for other neoplastic causes of intussusception, such as adenocarcinoma, lymphoma, and metastasis [3,4].…”
Section: Discussioncontrasting
confidence: 55%
“…On CT, lipomas and intussuscepted lipomas have been characterized by their fat density in a small number of case reports [1][2][3][4][5][6][7][8]. In our experience, however, not all intussuscepted lipomas maintain fat attenuation on CT after intussusception and may be mistaken for other neoplasms.…”
contrasting
confidence: 45%
“…However, these features are possible only in large lesions because the smaller ones are not detected due to artifacts and mostly partial volume averaging [4][5][6]. MR is particularly able in detecting fatty lesions because of signal intensity characteristics typical for adipose tissue, chiefly on T1-weighted and fat-suppressing images [7].…”
Section: Discussionmentioning
confidence: 98%
“…If the lesion is large, a correct preoperative diagnosis and planning by cross-sectional imaging are mandatory because endoscopy and barium enema may be inadequate [3]. Good specificity is reported in CT studies of large colonic lipoma [4][5][6]. However, few reports discuss the possibilities of MR imaging in diagnosing these lesions, even though this technique is considered very accurate in diagnosing fatty masses [7].…”
mentioning
confidence: 99%
“…Lipomas are the most common non-epithelial tumours of the colon (5). The incidence at autopsy is 0.2% (3,5).…”
Section: Discussionmentioning
confidence: 99%